The Challenge of Realizing Sustainable River Ecotourism to Improve Human Welfare and Protect Biodiversity in Indonesia - Azizah, Mutiara Nurul Lita; Wulandari, Desi (Indonesian Journal of Conservation, 2021)
AbstractEcotourism is ecologically sustainable tourism that focuses on managing nature to encourage understanding, appreciation, and conservation of the environment and culture. This paper analyzes the benefits of river ecosystems in Indonesia to improve human welfare and protect biodiversity through river ecotourism management towards sustainable living. Forms of river ecotourism that have been developed in Indonesia are white water rafting, observation of various flora and fauna, potential development in residential areas as an agenda for tracing and people's gardens, and making river flows an educational tourism idea. Realizing sustainable living river ecotourism can be done by diversifying tourism products. The success of river ecotourism is determined by three components, namely tourism performance, quality of tourism experience, and sustainable tourism. Efforts that can be made for sustainable living ecotourism such as holding innovative online courses for ecotourism managers and measuring the ecological footprint of ecotourism products.